2019
DOI: 10.2460/ajvr.80.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous administration of tiletamine-zolazepam, alfaxalone, ketamine-diazepam, and propofol for induction of anesthesia on cardiorespiratory and metabolic variables in healthy dogs before and during anesthesia maintained with isoflurane

Abstract: OBJECTIVE To compare effects of tiletamine-zolazepam, alfaxalone, ketamine-diazepam, and propofol for anesthetic induction on cardiorespiratory and acid-base variables before and during isoflurane-maintained anesthesia in healthy dogs. ANIMALS 6 dogs. PROCEDURES Dogs were anesthetized with sevoflurane and instrumented. After dogs recovered from anesthesia, baseline values for cardiorespiratory variables and cardiac output were determined, and arterial and mixed-venous blood samples were obtained. Tiletamine-zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…Time points T0, T30, T60, T90, T135 and T180 are statistically compared using Dunnett's multiple comparisons technique (at global a ¼ 0.05) Cardiovascular function was well maintained during anaesthesia with both protocols, although a significant decrease in HR was found at T30 compared with T0, and HR significantly decreased over time during anaesthesia with both protocols. In contrast, several authors reported an increase in HR when alfaxalone was administered as a single bolus (Morgaz Rodriguez et al 2012;Amengual et al 2013;Hampton et al 2019). A decrease of SAP and MAP was observed following induction of anaesthesia, for 90 minutes and 60 minutes, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Time points T0, T30, T60, T90, T135 and T180 are statistically compared using Dunnett's multiple comparisons technique (at global a ¼ 0.05) Cardiovascular function was well maintained during anaesthesia with both protocols, although a significant decrease in HR was found at T30 compared with T0, and HR significantly decreased over time during anaesthesia with both protocols. In contrast, several authors reported an increase in HR when alfaxalone was administered as a single bolus (Morgaz Rodriguez et al 2012;Amengual et al 2013;Hampton et al 2019). A decrease of SAP and MAP was observed following induction of anaesthesia, for 90 minutes and 60 minutes, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…This increase in Qt was associated to higher contractility and higher stroke volume index (Morgaz Rodríguez et al 2012). Tiletamine-zolazepam, ketamine-diazepam and propofol did not affect Qt and SVR (Hampton et al 2019a).…”
Section: Cardiovascular Effects Of Alfaxalonementioning
confidence: 80%
“…Both hypoventilation and hypoxaemia were reported after administering clinical doses of alfaxalone to dogs (Ambros et al 2008, Psatha et al 2011, Morgaz Rodríguez et al 2012, Maney et al 2013, Pinelas et al 2014, Barr et al 2017, Bigby et al 2017a,b, White & Yates 2017, Zapata et al 2018, Hampton et al 2019a but their severity was dose-dependent (Muir et al 2008). Similar respiratory complications were reported after propofol (Ambros et al 2008;Maney et al 2013;Barr et al 2017;Bigby et al 2017a,b;White & Yates 2017), etomidate (Morgaz Rodríguez et al 2012) and ketamine (White & Yates 2017) administration to healthy dogs, or after fentanyldiazepam-propofol administration to dogs with systemic disease (Psatha et al 2011).…”
Section: Respiratory Effects Of Alfaxalonementioning
confidence: 87%
See 1 more Smart Citation
“…However, tiletamine can cause depression in guinea pigs and rabbits (5,6). It is usually provided with zolazepam in veterinary settings as a narcotic sedative (tiletamine/zolazepam or Zoletil R ) for use as a shortterm anesthetic for surgical procedures in dogs (7)(8)(9). It has been observed that dexmedetomidine-butorphanol-tiletaminezolazepam (DBTZ) administered intramuscularly (IM) in healthy dogs rapidly induced short-term anesthesia and analgesia (7).…”
Section: Introductionmentioning
confidence: 99%